Pengaruh Tingkat Pendapatan, Lingkungan Sosial dan Kepercayaan pada Pemerintah Daerah Terhadap Kesadaran Membayar Pajak Bumi dan Bangunan Pedesaan Dan Perkotaan (PBB – P2) di Kelurahan Gunung Sarik Kota Padang - Ragita Cahyani; Ingra Sovita (CV. ITTC INDONESIA, 2024)
This research aims to determine and analyze the influence of income level, social environment and trust in local government on awareness of paying Rural and Urban Land and Building Tax (PBB – P2) in Gunung Sarik Village, Padang City, both partially and simultaneously. This research was conducted on PBB – P2 Taxpayers in Gunung Sarik District, using a quantitative approach. The sampling method is Simple Random Sampling with a sample size of 100 people. The data collection technique used is a questionnaire technique. The data analysis used is multiple linear regression. The research results show that the income level variable has a positive effect on awareness of paying PBB - P2, the social environment variable has a positive effect on awareness of paying PBB - P2 and trust in local government has a positive effect on awareness of paying PBB - P2. pay PBB - P2. Simultaneously, the variables of income level, social environment and trust in local government influence awareness of paying PBB – P2.